2013
DOI: 10.1111/jen.12037
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism at the cytochrome oxidase I gene in mediterranean populations of Batrocera Oleae (Diptera: Tephritidae)

Abstract: The tephritid Bactrocera oleae (Gmelin) is a harmful pest of olive crops that cause important agricultural and economic losses in the Mediterranean area where 90% of the world olive trees are cultivated. The knowledge of the genetic diversity in insect pest species populations is critical for decisions concerning appropriate control management strategies. In the present work, the genetic variability within and among 7 populations ‐five from Spain, one from Italy and one from Tunisia‐, was assessed by sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
2
12
0
1
Order By: Relevance
“…However, growing concerns over environmental damage, human health and the development of insect resistance are inducing a gradual shift towards more integrated pest control approaches. Under these circumstances, it is now generally accepted that a comprehensive understanding of olive fly's population structure and dynamics is crucial for the design of effective management and control strategies [ 7 , 8 , 9 ]. Previous genetic studies have established that there are three distinct Old World populations of B .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, growing concerns over environmental damage, human health and the development of insect resistance are inducing a gradual shift towards more integrated pest control approaches. Under these circumstances, it is now generally accepted that a comprehensive understanding of olive fly's population structure and dynamics is crucial for the design of effective management and control strategies [ 7 , 8 , 9 ]. Previous genetic studies have established that there are three distinct Old World populations of B .…”
Section: Introductionmentioning
confidence: 99%
“…There is also good evidence for the existence of population substructure in the latter region, but we are still far from a comprehensive view. Indeed, earlier studies [ 11 , 12 ] suggested three Mediterranean subpopulations ("Eastern", "Central" and "Western"), but pointed to substantial population admixture; later analyses, on the other hand, suggested deep separation of the mitochondrial DNA (mtDNA) lineages found in the three areas [ 13 , 14 ]; and two very recent studies [ 7 , 8 ], though providing further support for the distinction between populations, again raised the possibility of significant gene flow between them.…”
Section: Introductionmentioning
confidence: 99%
“…同时, 在条形码序列分析的基础上, 还研发出了 27 种检疫性实蝇的 SS-PCR [95,96] 技术、TaqMan MGB 实 时荧光 PCR 技术以及集成流路芯片鉴定技术, 基本 形成了较为完善的检疫性实蝇的分子鉴定技术体系. 此外, 采用 COI 基因序列比对及系统发育分析, 分别 对广西苦瓜(Momordica charantia L.)中的瓜实蝇幼虫 和南亚果实蝇(B. tau (Walker))幼虫 [97] 、 采自泰国的番 石榴实蝇(B. correcta (Bezzi))幼虫 [18] 、采自布迪隆的 入侵果实蝇 [98] 、进境越南西瓜(Citrullus lanatus)中截 获的瓜实蝇幼虫 [99] 及芒果(Mangifera indica L.)上的 入侵果实蝇幼虫和非洲芒果实蝇(C. cosyra Walker) 幼虫 [100] [104,105] 、 南 亚 果 实 蝇 [106] 、 油 橄 榄 实 蝇 (B. oleae Gmelin) [107,108] 、桃果实蝇(B. zonata (Saunders)) [109] 、 辣椒实蝇(B. latifrons (Hendel)) [110] 等的相关研究已有 陆续报道. 例如, 对橘小实蝇的系统研究显示, 该实 蝇从东南亚地区传入我国并进而向北扩张, 同时对 其入侵路径以及各区域的起源进行了预测 [111~114] .…”
Section: 在实蝇类害虫研究中的应用unclassified
“…To make methods for the control of fruit flies more efficient and safe, greater knowledge is needed on the structure and dynamics of the populations, as well as on the biogeography of the target species (Matallanas et al 2013, Hendrichs et al 2015. Current knowledge suggests that, in Colombia, A. fraterculus s.l.…”
Section: Introductionmentioning
confidence: 99%